Analysis of an isolated induction generator driven by renewable energy sources - Lu, Jun Wei. (2010)
Wind farms are typically used in areas where conventional means of electricity like grid power are not readily available. Wind power thus becomes the power generation method of choice due to the vast availability of unobstructed wind flow in remote areas. Due to the lack of a power supply, induction generators operating in such regions have to operate in a self-excited mode. In such areas, the wind speeds encountered by the wind turbines may vary greatly. As such, speed controllers that are able to regulate the torque generated by changing wind speeds to produce a more consistent output are used. This allows a wind turbine system where the generator experiences a regulated speed from the shaft of the prime mover to be used. The report details the student’s study on the use of three-phase squirrel-cage induction machines to produce three phase power in a typical wind farm setting with regulated wind speeds. The student will conduct an investigative analysis into various configurations that will allow the most efficient conversion of wind power to electrical power under such conditions. This report will detail what the student has learnt from his research and also show simulations of the induction motor model obtained from MATLAB Simulink.